The Effect of Adjuvant Pelvic Radiotherapy on Distant Metastasis for Uterine Carcinosarcoma. (April 2021) - Eng, Nina L.; Rana, Shushan R.; Hall, Kevin L.; Eng, Tony Y.
Abstract : Background: Uterine carcinosarcomas (UCS) are rare tumors that carry a poor prognosis and high recurrence rate. Standard treatment consists of surgical resection and chemotherapy, though the benefit of adjuvant radiotherapy (RT) has yet to be determined. This study assessed survival rates between patients with UCS who underwent surgical resection alone and patients who underwent combinations of surgery, chemotherapy, and RT. Materials and Methods: We conducted a retrospective review of all patients who underwent surgical resection for UCS between 1993 and 2011 at a single institution. We assessed 3-year disease-free survival, locoregional recurrence-free survival, distant metastases-free survival (DMFS), and overall survival rates and utilized Kaplan-Meier modeling to analyze differences between UCS treatment modalities. Results: Twenty-four patients underwent UCS surgical resection between 1993 and 2011. The mean age was 61 (range: 39 to 75 y). Of these patients, 100% (n=24) underwent surgical resection, 25% (n=6) underwent surgery and adjuvant chemotherapy, 29% (n=7) underwent surgery and adjuvant RT, and 33% (n=8) underwent surgery and adjuvant chemotherapy and RT. At 3 years median follow, there was no significant difference in overall survival between treatment modalities. The addition of radiation therapy conferred increased DMFS in patients undergoing surgery irrespective of adjuvant chemotherapy (44% vs. 83%, P =0.0211). In patients receiving adjuvant chemotherapy, the significant increase in DMFS persisted with the addition of RT ( P =0.0310). Lymph node involvement (n=8) was associated with a lower locoregional recurrence-free survival (38% vs. 92%, P =0.0029). Conclusions: RT may offer a potential benefit in reducing the rate of distant metastases, though there were no statistically significant improvements in survival metrics.